2016
DOI: 10.1021/acs.est.6b01187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microplastic on the Gills of the Shore Crab Carcinus maenas

Abstract: Microscopic plastic debris (microplastics, <5 mm in diameter) is ubiquitous in the marine environment. Previous work has shown that microplastics may be ingested and inhaled by the shore crab Carcinus maenas, although the biological consequences are unknown. Here, we show that acute aqueous exposure to polystyrene microspheres (8 μm) with different surface coatings had significant but transient effects on branchial function. Microspheres inhaled into the gill chamber had a small but significant dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(108 citation statements)
references
References 29 publications
(53 reference statements)
4
91
0
4
Order By: Relevance
“…It is likely that organisms will have varying thresholds in relation to changes in turbidity (Newcombe and Macdonald 1991;Gordon and Palmer 2015); therefore, deriving thresholds based on species sensitivity for suspended solids could provide useful insight in defining if effects observed are intrinsic to the particle or are representative of an intrinsic response of the organism to particles in general (Ogonowski et al 2018;ECETOC 2019). Although a few studies have addressed this specific question (Casado et al 2013;Ogonowski et al 2016;Watts et al 2016;Straub et al 2017), more research in defining appropriate particle controls appears warranted, which may help address concerns related to exposure to microplastic particles and responses that an organism may have to any particle, naturally occurring or synthetically derived (Ogonowski et al 2018;ECETOC 2019).…”
Section: Adverse Effects and Dose-response Relationshipsmentioning
confidence: 99%
“…It is likely that organisms will have varying thresholds in relation to changes in turbidity (Newcombe and Macdonald 1991;Gordon and Palmer 2015); therefore, deriving thresholds based on species sensitivity for suspended solids could provide useful insight in defining if effects observed are intrinsic to the particle or are representative of an intrinsic response of the organism to particles in general (Ogonowski et al 2018;ECETOC 2019). Although a few studies have addressed this specific question (Casado et al 2013;Ogonowski et al 2016;Watts et al 2016;Straub et al 2017), more research in defining appropriate particle controls appears warranted, which may help address concerns related to exposure to microplastic particles and responses that an organism may have to any particle, naturally occurring or synthetically derived (Ogonowski et al 2018;ECETOC 2019).…”
Section: Adverse Effects and Dose-response Relationshipsmentioning
confidence: 99%
“…The respiratory uptake and the following adhesion of MPs to the gills might influence the branchial function. For instance, Watts et al [58] found a significantly decreased oxygen consumption of MP-exposed crabs after 1 h and observed some adaptation as oxygen consumption returned to normal after 16 h.…”
Section: Other Crustaceansmentioning
confidence: 99%
“…In addition to blocking the digestive tract and preventing normal feeding, microplastic ingestion can damage the cells and tissues of organisms such as blue mussels (von Moos et al, 2012), and crustaceans (Laist, 1987). Watts et al (2016) found that the ingested microplastics by shore crabs (Carcinus maenas) affect the respiratory function. Fishes swallow MPPs (Wright et al, 2013a), which may severely damage and/or kill fishes.…”
Section: Ecological Implicationsmentioning
confidence: 99%